EFFECTIVENESS OF EXPRESSIVE WRITING FOR EMOTION REGULATION IN ADOLESCENTS - Asiva Salma; Panca Kursitin Handayani; Nurlaela Widyarini (P3I UMSurabaya, 2024)
This study aimed to assess the effectiveness of expressive writing in improving emotional regulation in adolescents with low emotional regulation. A quantitative experimental design was employed using a pre-experiment approach with a one-group pretest-posttest design. The participants were 4 adolescents (2 males, 2 females) with low emotion regulation, as measured by the Emotion Regulation Questionnaire (α=0.664). The intervention involved four stages of expressive writing: recognition, examination, juxtaposition, and application to self. The results indicated a significant improvement in emotional regulation post-intervention (t = -8.392, p < 0.05). The findings suggest that expressive writing can be an effective preventive intervention for adolescents with low emotional regulation.